2006
DOI: 10.1122/1.2167448
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear rheology of styrene-butadiene rubber filled with carbon-black or silica particles

Abstract: The nonlinear rheology of styrene-butadiene rubber filled with carbon-black or silica particles is investigated by complementary viscosimetric devices on a wide range of deformation and deformation rates. The effect of filler volume fraction on the rheological behaviour is systematically studied. The importance of a critical volume fraction (percolation threshold) is outlined, giving rise to a network structure at rest. At finite deformation, this structure is destroyed and the compounds exhibit a non-linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Above τ c , the curves are also superimposed, but this is due to the existence of a plateau. The same behavior may be seen on the results of Mongruel and Cartault , even though the authors did not discuss these two regimes. Gierlowski et al also observed on a pure SBR a similar behavior, but without a plateau.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Above τ c , the curves are also superimposed, but this is due to the existence of a plateau. The same behavior may be seen on the results of Mongruel and Cartault , even though the authors did not discuss these two regimes. Gierlowski et al also observed on a pure SBR a similar behavior, but without a plateau.…”
Section: Resultsmentioning
confidence: 92%
“…Malkin et al proved for a SBR compound that wall slip was always observed at low temperature (70°C), whereas above 110°C, it occurred only above a critical shear stress of 0.3 MPa. Mongruel and Cartault investigated the effect of carbon black content on the rheological behavior of SBR in a temperature range from 70°C to 130°C. They proved that the time‐temperature superposition principle was valid whatever the filler content, with the same shift factor as for the pure rubber.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] At strains substantially below where the neat polymer shows nonlinearity in its mechanical response, the nanocomposite becomes nonlinear. [1][2][3][5][6][7] The origin of these phenomena is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Modified-clay nanocomposites exhibited a lower die swell than unmodified nanocomposites, which was attributed to better dispersion/exfoliation of modified-clay in the rubber matrix. Most importantly, here will show that the extrudate swell of the composite can be expressed as that of the corresponding matrix polymer multiplied by a coefficient which is similar to the concentration shift factor used in describing the dynamic modulus variation with the filler loading level [15]. …”
Section: Introductionmentioning
confidence: 99%